A Chance to Show His Mettle: War, Creativity and Reparation in the Work of Wilfred Bion. (15th July 2016) - Ballinger, Caroline
Abstract : This paper looks in detail at Wilfred Bion's war writings, specifically at his preoccupation with issues of morale and leadership, and at the intense feelings of isolation and disillusionment that accompany his bleakest moments. This reading of the war writings demonstrates that Bion found resources that enabled him not only to survive this harrowing time but also to work creatively to improve the lives of his fellow soldiers, and it is suggested that Melanie Klein's concept of unconscious reparation may be helpful in considering Bion's life and work during this period. An impulse to repair may also be discerned in Bion's first published paper, 'The "war of nerves"…' (1940 ), as well as in his work in 1942 for the War Office Selection Board where, with the support of gifted army leaders, Bion was able to draw on his traumatic wartime experiences in order to make influential contributions to the reform of the British Army.